Design, fabrication and characterisation of Si‐based capillary‐driven microfluidic devices. (1st December 2018) - Ye, Yifei; Zhao, Yang; Cheng, Jie; Li, Mingxiao; Huang, Chengjun
Abstract : Capillary‐driven microfluidic devices have a great potential for the point‐of‐care testing systems based on the advantages of self‐pumping, low reagent usage and rapid detection. Here, the study presents a lidless Si‐based capillary‐driven microfluidic device, comprising two inlets for sample and buffer loading, a snake‐shaped microchannel (120/0.05/0.025 mm in length/width/depth) as a flow resistor, a micropillar array (25/5/8 μm in height/diameter/pitch) as a capillary pump and a vent. It was fabricated with lithographic technique in combination with deep Si etch technique. A simple and stable surface hydrophilisation modification method was demonstrated on the device by forming a self‐assembly monolayer through Cu‐catalysed azide‐alkyne cycloaddition reaction. The surface modified device allowed controllable autonomous capillary flow delivery with a contact angle of around 40° stabilised for at least 90 days. The design of two inlets with one common long snake‐shaped microchannel provided the sequential capillary flow generation and propagation with controlled flow rate and propagation distance, while the micropillar array with a high aspect ratio of 5 was considered as an effective capillary pump. Based on the obtained results, the proposed device makes possible for the on‐chip biosensing applications as a part of integrated point‐of‐care testing systems.